2003
DOI: 10.4018/978-1-59140-061-5.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Introduction of Electronic Banking in Egypt Using the Technology Acceptance Model

Abstract: The developments taking place in information and communication technology are increasing competition in financial institutions worldwide. Thus, the deployment of advanced technologies is essential to achieve a competitive edge. Recently, the banking industry was highly affected by the technology evolution that transformed the way banks deliver their services, using technologies such as automated teller machines, phones, the Internet, credit cards, and electronic cash. In line with global trends, retail banking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 11 publications
(10 reference statements)
4
22
0
2
Order By: Relevance
“…According to Davis (1989), it is expected that perceived usefulness and perceived ease of use will influence intention to use e-democracy Web sites. Kamel and Hassan (2003), Al-Sukkar and Hasan (2005) and Vatanasombut et al (2008) Ayo et al (2011) found perceived usefulness and perceived ease of use as positive antecedent of intention to use. Therefore, the following hypotheses are proposed:…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…According to Davis (1989), it is expected that perceived usefulness and perceived ease of use will influence intention to use e-democracy Web sites. Kamel and Hassan (2003), Al-Sukkar and Hasan (2005) and Vatanasombut et al (2008) Ayo et al (2011) found perceived usefulness and perceived ease of use as positive antecedent of intention to use. Therefore, the following hypotheses are proposed:…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…However, other related research Chau, 1996) also argues that the influences of PEOU on PU diminish over time, as user proficiency with a technology increases (Kamel & Hassan, 2003). Kamel and Hassan therefore conclude that the TAM is appropriate in explaining the attitudes and usage intention of users during the early stage of adoption but fails to consider the contextual influences such as culture and technology accessibility and affordability, which can affect the extent of use in post-adoption.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…Beyond TAM's basic constructs, perceived ease of use and perceived usefulness, other contextual factors may alter user acceptance of technology (Kamel & Hassan, 2003;Bhatti, 2007). These contextual factors include the availability of enabling technologies for effective, the affordable provision of mobile services, and cultural nuances that influence technology adoption (Boadi et al, 2007).…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…In a study of customer preferences for different delivery channels, by [42] found that customers ranked ATMs to be the most important delivery channel, with 70.65% of respondents regarding them as extremely important; bank branches came in second position, then mbanking and finally Internet banking, with only 17.39% of respondents regarding it as an extremely important delivery channel [7]. Another study by [43] revealed that most of the Self-Service Banking Technologies [SSBTs] users used ATMs in preference to Mobile and Internet banking.…”
Section: Related Workmentioning
confidence: 99%